2000
DOI: 10.1007/s004040000076
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer in young Japanese women

Abstract: This study was performed to determine whether the incidence of cervical cancer in women aged 35 or younger has changed over the last 10 years and to examine the clinical characteristics of the cases. The incidence of cervical cancer in women aged 35 or younger were significantly greater in 1987-1991 than 1992-1996 (p = 0.001). Most new cases were detected by routine cytological screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Many reports have suggested that the incidence of cervical cancer in young women is continuing to increase steadily [23][24][25]. The majority of invasive cancers are squamous cell carcinomas, although greater prevalence of adenocarcinoma and adenosquamous carcinoma in young women have been reported [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have suggested that the incidence of cervical cancer in young women is continuing to increase steadily [23][24][25]. The majority of invasive cancers are squamous cell carcinomas, although greater prevalence of adenocarcinoma and adenosquamous carcinoma in young women have been reported [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase in the incidence of cervical cancer among young women in the developed countries (Wright et al 1994;Hamasaki et al 1998;Morimura et al 1998;Anttila et al 1999;Ito et al 2000). Very recently, the Ministry of Health, Labor and Welfare proposed that cervical cancer screening should be conducted for women aged 20 to 29 years old even in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been an increase in incidence of cervical cancer among young women in Japan. While the overall morbidity rate of cervical cancer has been declining, the morbidity rate in the 20's and 30's age groups has been rising (Wright et al 1994;Hamasaki and Yoshida 1998;Morimura et al 1998;Sato et al 1998;Ito et al 2000; Miyagi Cancer Society subjects who required close examination, 34 cases underwent treatment, and 17 cases were under age 30. Moreover, all three cases of microinvasive and/or invasive carcinoma were under the age of 30 years (23, 23, 27 years old, respectively).…”
mentioning
confidence: 99%
“…Although a substantial decrease in both incidence and mortality rates has been observed in the past 30 years, with the age of patients becoming increasingly younger (2,3). More than 100,000 cervical cancer cases are diagnosed in China each year, and lymph node metastasis is the most common form of metastasis in the early stages of cervical cancer (4).…”
Section: Introductionmentioning
confidence: 99%